Distribution and Marketing Margin Analysis of Cinnamon in Tidore City - Kaddas, Fatmawati; Baguna, Firlawanti Lestari (Agrikan Jurnal Agribisnis Perikanan, 2023)
Tidore Islands City Most of its residents earn income from cinnamon farming. Cinnamon trees are peeled and the process of drying cinnamon is carried out to dry. Cinnamon is sold in stick form and involves marketing institutions. Cinnamon bark is used as a spice ingredient such as food mixes, cake making, drinks, medicines and aroma therapy. The purpose of this study is to identify marketing channels in the study area, to analyze the amount of marketing costs and margins of each marketing channel. The research was conducted in Tidore Island, Tidore Islands City, North Maluku Province in 2022. Farmer respondents were taken by census while traders used snowball sampling method. Data were analyzed using marketing margin analysis, marketing cost, marketing profit and farmer's share. Distribution research and cinnamon marketing margin in Tidore City there are 3 models of marketing channel distribution which involve various marketing institutions. The value of cinnamon marketing margins at the farm level in each channel, respectively, amounted to Rp11,050/bunch. While other marketing actors range from Rp5,000 - 20,000 / bunch depending on the profit and the pattern of marketing channels for cinnamon products. While the farmer's share of cinnamon products shows that the marketing channel is efficient, by showing marketing channel 1 the share received by farmers reaches 44.2%. The highest profit to cost ratio in marketing channel 2 was 372.13.